Peningkatan Pengetahuan Perilaku Hidup Bersih dan Sehat melalui Edukasi Interaktif pada Siswa Kelas 2 SD Dharma Loka Pekanbaru - Dona Martilova; Atika Atika; M. Rendy Ramadhan; Putri Nur Annisa; Salma Asilah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Clean and Healthy Living Behavior (PHBS) is an important component in creating healthy living habits, especially in elementary school children. Education about PHBS needs to be instilled from an early age to form a sustainable healthy lifestyle. This study aims to determine the effect of interactive education on improving the understanding of second-grade students at Dharma Loka Elementary School Pekanbaru regarding PHBS. In this study, 50 students were involved using a pre-experimental design through the One Group Pretest-Posttest Design method. The educational intervention was carried out using interactive instructional games such as snakes and ladders, animated films, and PowerPoint presentations. The results showed an increase in students' understanding of PHBS after the intervention. The average score of students in the initial test was 93.2, while after the intervention, the average score increased to 100, with an increase of 6.8 points. This indicates that interactive learning has a positive impact on students' understanding of PHBS. Learning that involves teaching aids and games is proven to be more interesting for elementary school students, making them more active in the learning process. Interactive education not only improves students' understanding but also encourages them to apply PHBS more in their daily lives. The use of media such as games, animated films, and PowerPoint presentations facilitates a more comprehensive and enjoyable understanding. Therefore, this approach can be an effective strategy for teaching children healthy lifestyles, while providing a fun and rewarding learning experience. This interactive education also provides students with the opportunity to learn in a more enjoyable and less boring way. Through the snakes and ladders game, students can learn the concept of healthy living (PHBS) directly in a lighter and more entertaining way. Animated films and PowerPoint presentations add variety to the learning method, making the information conveyed more easily by students.